Strategic Management Strengthens Sustainable Educational Tourism Schools and Student Environmental Entrepreneurship: Manajemen Strategis Memperkuat Sekolah Pariwisata Pendidikan Berkelanjutan dan Kewirausahaan Lingkungan Siswa - Indri Ribbut Aprilla; Amrozi Khamidi; Mohammad Syahidul Haq; Muhammad Sholeh; Kaniati Amalia; Rusijono Rusijono (Universitas Muhammadiyah Sidoarjo, 2026)
Educational tourism programs embedded in schools are increasingly promoted to deliver experiential learning, yet many institutions struggle to sustain them amid limited resources, uneven stakeholder commitment, and weak strategic alignment. This study aims to explain how strategic management practices enable sustainable educational tourism schools while strengthening student character education and environmental entrepreneurship. Using a qualitative multiple-case design, data were collected in two junior high schools implementing educational tourism initiatives through semi-structured interviews with school leaders, teachers, students, parents, and program teams, complemented by onsite observations and document analysis. Thematic analysis indicates that program sustainability is achieved through a participatory strategic management cycle that integrates vision-driven planning, structured implementation with clear task allocation, and periodic evaluation used for continuous adjustment. Empirically, the programs improve students’ environmental literacy, creativity, responsibility, and entrepreneurial orientation through hands-on activities such as eco-farming, waste-to-resource practices, and student-managed production units. A key novelty of this study is its comparative, end-to-end mapping of strategic management processes across two educational tourism school models, demonstrating how adaptive evaluation and stakeholder collaboration jointly compensate for constraints in funding and human resources. The findings advance theory by linking strategic management cycles to experiential character learning outcomes, and they inform policy and practice by recommending stronger cross-sector partnerships, capacity development for teachers and students, and data-informed monitoring to institutionalize sustainable educational tourism in secondary education. Highlights: Participatory strategic management offsets resource constraints through multi-stakeholder collaboration. Continuous evaluation strengthens program sustainability and accelerates learning innovation. Educational tourism improves environmental literacy, creativity, and student entrepreneurship. Keywords: Strategic Management, Educational Tourism, Stakeholder Collaboration, Character Education, Environmental Entrepreneurship